129k views
2 votes
Substitution method​

Substitution method​-example-1
User Basak
by
5.3k points

2 Answers

5 votes

Answer:

(22, 5)

Explanation:

Given the 2 equations

x = y + 17 → (1)

x = 4y + 2 → (2)

Substitute x = 4y + 2 into (1)

4y + 2 = y + 17 ( subtract y from both sides )

3y + 2 = 17 ( subtract 2 from both sides )

3y = 15 ( divide both sides by 3 )

y = 5

Substitute y = 5 into either (1) or (2) and solve for x

(1) : x = 5 + 17 = 22

Solution is (22, 5)

User Icasimpan
by
5.9k points
5 votes

The answer will be

X=22, Y=5

Hope this help

User Yasmin
by
5.3k points